MODEL PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF (MMI) UNTUK MENINGKATKAN PENGUASAAN KONSEP DAN KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI OPTIK - R. Rahmatiah; Gunawan Gunawan; Sutrio Sutrio (Universitas Pendidikan Mandalika, 2013)
This study is an experimental study that aims to determine the increasing of concept mastery and the students critical thinking skills in Optical materials using Interactive Multimedia (MMI) based learning model. Optical materials in this study is limited to the Geometry Optics material. Research design using pre-test - post-test control group design. The population in this study were all students of class X SMA Negeri 2 Mataram Academic Year 2012/2013. Sampling using random cluster sampling, the students of class X-1 as the experimental group and the students of class X-3 as a control group. The increasing data of concepts mastery and critical thinking skills of students were analyzed using t-test formula two parties polled variance and N-gain test. At the significant level of 5% and dk of 79 obtained that ttest is more than ttable (5.198> 1.993). It is obtained for the experimental class N-gain of 71.338% with a high category, whereas for the control class derived N-gain of 60.261% with moderate category. Thus, it can be concluded that the increasing mastery of concepts and critical thinking skills of students in the material Optics, Optics Geometry in this case, in experiments class using the Interactive Multimedia-based learning model (MMI) is higher than in the control class that uses a conventional learning models.